Partially Overlapping Mechanisms of Language and Task Control in Young and Older Bilinguals - Weissberger, Gali H. (2012)
The current study tested the hypothesis that bilinguals rely on domain-general mechanisms of executive control to achieve language control by asking if linguistic and nonlinguistic switching tasks exhibit similar patterns of aging-related decline. Thirty young and 30 aging bilinguals completed a cued language-switching task and a cued color-shape switching task. Both tasks demonstrated significant aging effects, but aging-related slowing and the aging-related increase in errors were significantly larger on the color-shape than on the language task. In the language task, aging increased language-switching costs in both response times and errors, and language-mixing costs only in response times. In contrast, the color-shape task exhibited an aging-related increase in costs only in mixing errors. Additionally, a subset of the older bilinguals could not do the color-shape task, but were able to do the language task, and exhibited significantly larger language-switching costs than matched controls. These differences, and some subtle similarities, in aging effects observed across tasks imply that mechanisms of nonlinguistic task and language control are only partly shared and demonstrate relatively preserved language control in aging. More broadly, these data suggest that age deficits in switching and mixing costs may depend on task expertise, with mixing deficits emerging for less-practiced tasks and switching deficits for highly practiced, possibly “expert” tasks (i.e., language).